Ideologia del gender? Alcuni profili di ordine giuridico-canonico (Stato, Chiese e pluralismo confessionale, 2017)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa â 2. Concetto di identitÃ  sessuata â 3.Â Riverberi sul piano teologico e canonico â 4. Conclusioni.Gender ideology? Some legal-canonical order profilesABSTRACT: Today we are facing the threat of a new modus pensandi, which has already achieved its objectives in Europe and in Italy: the gender theories. The latter are intended to assert the superiority of culture over nature, aiming for the recognition of the third kind. In Europe they have already succeeded in their aim, while in Italy we need to reflect more on the term person, focusing on the fact that culture must lie in the nature, only certainty of our existence. Hopefully, starting from Italy, also Europe returns 'his steps'.
Keywords: Bioetica e diritto